Triangularity of nuclear arms control: Possible implications of China’s involvement in nuclear arms talks - G. Savelyev, Alexander (AEI Insights, 2021)
Beijing explains its firm unwillingness to join the United States and Russia in nuclear arms control talks by the fact that China’s nuclear arsenal is incomparable with respective potentials of the world’s two leading nuclear powers. China urges Russia and the U.S. to go ahead with the nuclear disarmament process on a bilateral basis, and promises it will be prepared to consider the possibility of its participation in the negotiations only when its counterparts have downgraded their arsenals approximately to China’s level. Washington finds this totally unacceptable and demands that China either join the existing Russian-U.S. strategic New START treaty right away or agree to enter into a trilateral nuclear arms control format. This article studies the prospects of China’s involvement in nuclear arms talks and analyzes the true reasons behind Beijing’s desire to avoid any nuclear disarmament deals at this point. The working hypothesis of this paper is that China’s stance on the above issue is by no means farfetched or propagandistic, and that it is driven by fundamental political, military and strategic considerations. Disregard for this factor and further forceful efforts to bring China to the negotiating table to discuss nuclear arms control will lead to failure.